1988
DOI: 10.1016/0735-1097(88)90292-6
|View full text |Cite
|
Sign up to set email alerts
|

The automatic implantable cardioverter defibrillator: Efficacy, complications and survival in patients with malignant ventricular arrhythmias

Abstract: Ninety-four patients underwent surgery for automatic implantable cardioverter-defibrillator implantation. Ninety patients were discharged from the hospital with the device and were followed up for a mean period of 17 +/- 10 months. Forty-six patients experienced at least one discharge of the device under circumstances consistent with a malignant ventricular arrhythmia. One sudden death occurred. Complications included perioperative death (3 patients), post-operative ventricular tachycardia (12 patients) and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…52 However, underreporting is unlikely to be the cause for our finding that antiarrhythmic drug use, especially amiodarone, is associated with high defibrillation thresholds since the prevalence of antiarrhythmic drug use, including amiodarone, in our patients does exceed that in most other previously reported series. [53][54][55][56]58 Interestingly, in the one study in which amiodarone use was more frequent than in our study, patient entry was restricted to those with defibrillation thresholds .20 J,57 i.e., patients with high defibrillation thresholds were excluded.…”
Section: Study Limitationsmentioning
confidence: 99%
“…52 However, underreporting is unlikely to be the cause for our finding that antiarrhythmic drug use, especially amiodarone, is associated with high defibrillation thresholds since the prevalence of antiarrhythmic drug use, including amiodarone, in our patients does exceed that in most other previously reported series. [53][54][55][56]58 Interestingly, in the one study in which amiodarone use was more frequent than in our study, patient entry was restricted to those with defibrillation thresholds .20 J,57 i.e., patients with high defibrillation thresholds were excluded.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In fact, this therapy is now widely applied in clinical practice and considered by some to be the treatment of choice in cardiac arrest survivors.22-24 Previous studies have reported a low incidence of sudden See p 1348 cardiac death in patients with life-threatening ventricular arrhythmias who receive an implantable defibrillator. [25][26][27] However, since the introduction of the implantable defibrillator into clinical practice in the early 1980s, no large studies have specifically examined the impact of this new therapy on the long-term outcome of survivors of out-of-hospital cardiac arrest. The objective of this study was to examine the influence of the implantable defibrillator and other variables on long-term outcome in survivors of out-of-hospital cardiac arrest.…”
mentioning
confidence: 99%
“…The incidence of supraventricular arrhythmias causing device therapy is reported to be 20% to 30% [7,8]. Despite the use of antiarrhythmic drugs and programming of the arrhythmia discrimination algorithms, the incidence of inappropriate ICD therapies remains high.…”
Section: Inappropriate Therapiesmentioning
confidence: 98%